Strategi Penyelesaian Pembiayaan Bermasalah Produk Pembiayaan Mudharabah Pada PT. BPRS Gebu Prima - Tri Nurhalizah; Selamat Pohan (CERED Indonesia Institute, 2022)
The distribution of funds by Islamic banks and UUS in accordance with sharia principles carries the risk of default or late payment. Financing risk is the risk that arises as a result of the failure of the party to be financed (participant) in fulfilling its obligations. Problem financing is financing that has difficulty in repayment due to intentional factors or factors or conditions beyond the ability of the debtor. The purpose of this study was to find out what are the factors that cause problems in mudharabah financing products at PT. BPRS Gebu Prima and to find out how the problem solving strategy for mudharabah financing products at PT. BPRS Gebu Prima. This type of research uses descriptive qualitative research methods. The factors causing the problem of Bmudharabah financing are difficulties, marketing difficulties, declining income, miscalculation of opinions. Problem solving strategy by conducting deliberation with customers and using 3R (Restructuring, Rescheduling and Reconditioning).